ST2/IL-33 axis blockade inhibits regulatory T cell cytotoxicity towards CD8 T cells in the leukemic niche - Hua Jiang; Denggang Fu; Santhosh Kumar Pasupuleti; Baskar Ramdas; Alan Long; Abdulraouf M. Ramadan; Jinfeng Yang; Ramesh Kumar; Jessica H. Hartman; B. Jacob Kendrick; Ed Simpson; Hongyu Gao; et al. (Nature Communications)
Abstract Acute myeloid leukemia (AML) patients present with CD8 exhaustion signatures, and pharmacologic inhibition of checkpoints can have therapeutic benefit. The alarmin IL-33 and its receptor STimulation-2 (ST2) promote activation of tissue-regulatory T cells (Treg cells) and accelerate malignant progression in solid tumors, but their role in leukemia remains unclear. Here, we show that ST2+ Treg cells are enriched in bone marrow (BM) of humans and mice with AML and promote CD8+ T cells depletion and exhaustion. ST2 deficiency in Treg cells restores CD8+ T cell function, decreasing AML growth via retention of ST2+ Treg cells precursors in lymph nodes. AML-activated ST2+ Treg cells lack T-bet, IFN-γ and Bcl-6, and kill intratumoral CD8+ T cells by amplified granzyme B-mediated cytotoxicity compared to non-AML primed Treg cells. Engineered anti-ST2 antibodies induce ST2+ Treg cells apoptosis to extend survival in AML models. Together, our findings suggest that ST2 is a potential checkpoint target for AML immunotherapy.